Guanyin and the Gospel: Resonance Between Buddhism and Christianity on the Issue of “Relieving Suffering and Distress” - CHEN, Jian (Journal of Research for Christianity in China (JRCC), 2025)
In this article, it discusses that helping people in distress is a common relig- ion relationship of Buddhism and Christianity. According to a contrast of “Guanyin” and “Good news”, this paper also explores the problem of Christianity in China. The author believes Chi- nese Buddhism is a Chinese religion which present as Buddhism style, and Chinese Christianity is a an chinese religion which present itself as Christianity style. Therefore, based on the same content, christianity and Buddhism look like different on exterior , but the results are the same. Also, according to the translation of the Buddhism classic materials, the author believes chinese christianity must cut off the western culture in order to build a complete chinese style christianity. The chinese christianity must listen the God’s words from this time forth and for evermore.